A Holistic Approach to the Assessment of Sanitation Development in Mexican Villages - Tiberghien, Jacques-Edouard (Cranfield University, 2002)
Lack of, or inadequate sanitation development is a serious issue worldwide, especially in developing countries, where it severely affects human health, the environment and the economy. Despite the 'Water Decade' (1980-1990) and the repeated commitment of the international community to address sanitation development as a priority, the proportion of people enjoying good sanitary conditions in developing countries has not improved during the 1990s. During the last 30 years, post-colonial engineering-oriented approaches to sanitation development were gradually supplanted by multidisciplinary strategies. However, the specialists (e.g. engineers, epidemiologists, economists, sociologists, anthropologists, etc.) involved in development programs tend to view sanitation development from the narrow perspective of their respective discipline. As a consequence, sanitation development is perceived in a fragmented way. This research assumes that this fragmented perception is a major cause of the current state of sanitation worldwide and proposes to improve the understanding of sanitation development by viewing it as a whole. A methodology principally based on qualitative methods of investigation was set up to assess sanitation development in a holistic way. This approach was then tested on three communities in Central and South Mexico. For each case study, the main factors influencing sanitation development and their relationships were identified and organised graphically on paper in the form of conceptual maps. The holistic approach to the assessment of sanitation development is comprehensive and transparent. Despite some weaknesses, the conceptual maps successfully highlight the diversity and the interconnectedness of the factors influencing sanitation development. This research identifies major political, cultural, or economic factors hindering sanitation development throughout Mexico and explains how they interact as a system. As a consequence, this study constitutes an original and valuable attempt to counterbalance the habit of breaking up sanitation development into distinct and separate disciplines. It calls for more interaction in development programs, converting multidisciplinary teams into interdisciplinary teams. Although this study efficiently tackles the fragmented perception issue, a deeper insight into sanitation development can be gained by addressing it in more detail from critical macro-economic and macro-political perspectives. Testing of the holistic approach to the assessment of sanitation development in the context of real life projects is required to validate its usefulness as a decision-making aid.